Acid-Base Diagrams - Kahlert, Heike; Scholz, Fritz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Understanding acid-base equilibria made easy for students in chemistry, biochemistry, biology, environmental and earth sciences. Solving chemical problems, be it in education or in real life, often requires the understanding of the acid-base equilibria behind them. Based on many years of teaching experience, Heike Kahlert and Fritz Scholz present a powerful tool to meet such challenges. They provide a simple guide to the fundamentals and applications of acid-base diagrams, avoiding complex mathematics. This textbook is richly illustrated and has full color throughout. It offers learning features such as boxed results and a collection of formulae.
The math behind the pH-logci diagrams -- Constructing pH-logci diagrams -- The application of pH-logci diagrams for graphical estimation of the pH of solutions and for the derivation of simplified equations -- The use of pH-logci diagrams for the construction of titration diagrams -- Titration errors.
Keywords: Chemistry; Analytical biochemistry; Chemistry, inorganic; Chemistry, Physical organic; Geochemistry; Biochemistry; Environmental chemistry; Chemistry; Analytical Chemistry; Biochemistry, general; Environmental Chemistry; Inorganic Chemistry; Physical Chemistry; Geochemistry